Biosynthesis and genome mining strategies for purine-derived N-nucleoside antibiotics - Wu, Yujie; Wu, ShiYu; Niu, Xiaomin; Yu, Xue; Chen, Tuo; Liu, Guangxiu; Zhang, Wei (Frontiers in Microbiology, 2025)
BackgroundThe rise of antibiotic resistance underscores the urgent need for new antimicrobial agents. Nucleoside antibiotics are a structurally diverse class with broad biological activities, among which purine-derived N-nucleoside antibiotics (N-NAs) are of particular interest as their purine-linked frameworks enable diverse enzymatic modifications that yield compounds with distinct pharmacological profiles.Aim of the reviewThis review summarizes the bioactivity and biosynthetic logic of representative purine-derived N-NAs, including pentostatin-type compounds, angustmycins, and deazapurine analogues, to provide insights into the genome-based discovery of related natural products.Key scientific concepts of the reviewBy outlining conserved enzymes and genetic features within known BGCs, we illustrate how core enzyme probes can be used for genome-guided mining of putative clusters. This approach emphasizes both the opportunities and challenges in predicting novel N-NA producers from genomic data.ConclusionUnderstanding the biosynthesis and genetic organization of N-NAs not only sheds light on their structural diversity but also provides a framework for genome mining. Specific subclasses such as pentostatin-, angustmycin-, and deazapurine-type compounds exhibit Structure–Activity relationships that could guide the rational design and genome-based discovery of new nucleoside antibiotics.